Erotic Fiction and Christian Sexual Ethics in Nonnus’ Episode of Morrheus and Chalcomede - Hadjittofi, Fotini (2016)
The extensive episode of Morrheus and Chalcomede, which covers books 33-35 of Nonnus’ fifth century epic, the Dionysiaca, has almost all the ‘ingredients’ of a novel. This paper emphasises the way Nonnus re-formulates, adapts, and subverts novelistic themes throughout this episode, thus showing the gap between contemporary sexual ethics, where perpetual female virginity is glorified, and the ideology of marriage which drives the plots of the earlier erotic novels. The empowerment and masculinisation of the devoted virgin, Chalcomede, and the corresponding powerlessness and feminisation of the male hero, Morrheus find parallels (and, in the final scene, perhaps also inspiration) in Christian texts.